(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine the structure of desire of the main character in the short story "Tiurmaida" by Hasan Al-Banna using Jacques Lacan’s psychoanalytic theory. The analysis focuses on narcissistic desire that emerge in Tiurmaida, a loyal and strong wife. This study uses a qualitative descriptive method with a literary psychology approach. The results of the study indicate that Tiurmaida has active and passive narcissistic desire. Active narcissistic desire is seen in her efforts to show herself as a loyal wife and a strong woman, while passive narcissistic desire is seen in her dependence on recognition from others. This study shows that human desire always has a paradoxical nature and is closely related to the social, symbolic, and psychic structures that surround it